2011
DOI: 10.1186/1472-6793-11-16
|View full text |Cite
|
Sign up to set email alerts
|

VEGF signaling mediates bladder neuroplasticity and inflammation in response to BCG

Abstract: BackgroundThis work tests the hypothesis that increased levels of vascular endothelial growth factor (VEGF) observed during bladder inflammation modulates nerve plasticity.MethodsChronic inflammation was induced by intravesical instillations of Bacillus Calmette-Guérin (BCG) into the urinary bladder and the density of nerves expressing the transient receptor potential vanilloid subfamily 1 (TRPV1) or pan-neuronal marker PGP9.5 was used to quantify alterations in peripheral nerve plasticity. Some mice were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 60 publications
3
29
0
4
Order By: Relevance
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that animal models of urinary bladder inflammation and BPS/IC regulate the VEGF-VEGF receptor system in the urothelium (Cheppudira et al, 2008; Malykhina et al, 2012; Saban et al, 2008a; Saban et al, 2011; Saban et al, 2010; Saban, 2015; Saban et al, 2008b). Increased expression of VEGF and receptors has been reported in bladder biopsies from women with BPS/IC and expression of VEGF correlates with pain described by patients (Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In CYP-induced cystitis, the VEGF-VEGF receptor system is increased in the urothelium and chronic urothelial overexpression of NGF increases VEGF receptor and protein expression in the urothelium and detrusor smooth muscle (Cheppudira et al, 2008). Intravesical instillation of VEGF produced bladder inflammation, increased voiding frequency, increased abdominal sensitivity and increased bladder nerve density in specific nerve populations including TRPV1-, substance P-, and calcitonin gene-related peptide-immunoreactive nerve fibers (Malykhina et al, 2012; Saban et al, 2011). Other roles for VEGF-VEGF receptor system in the lower urinary tract may involve inflammation-induced lymphangiogenesis and angiogenesis (Saban et al, 2010; Saban, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in mouse bladder inflammation induced by BCG (bacille Calmette-Gu erin) instillation, a significant increase in peripheral nerve density and protein gene product 9.5 can be abolished by pretreatment with anti-VEGF neutralizing antibody. 16 The VEGF pathway is likely to mediate bladder neuroplasticity and inflammation in response to BCG.…”
Section: Commentmentioning
confidence: 99%
“…Сред-няя оценка по международной системе SCORAD со-ставила (41,46 ± 26,42) балла. Большинство детей имели сопутствующие аллергические заболевания: аллерги-ческий ринит -73,33 %, бронхиальную астму -13,33 %, острая крапивница зарегистрирована в анамнезе у 3 больных (10 % [5,7,8]. Причем кон-центрация данного цитокина коррелирует со степенью тяжести заболевания (r = 0,49).…”
Section: результаты исследования и их обсуждениеunclassified
“…Так, у пациентов с ограниченной фор-мой его величина равна (113,08 ± 29,23) пг/мл, тогда как при распространенном и диффузном процессах зна-чения гораздо выше [(319,32 ± 32) пг/мл и (812,60 ± 221,40) пг/мл]. Возможно, это связано с тем, что VEGF не только оказывает влияние на развития кровеносных сосудов кожи, но и является аутокринным регулятором гиперплазии эпидермиса [8], что проявляется в виде обширных очагов лихенификации у обследованных нами пациентов.…”
Section: результаты исследования и их обсуждениеunclassified